Investimento estrangeiro direto no Brasil (1990-2002): aspectos sócio políticos - Moura Junior, Álvaro Alves de (2010)
This thesis aims to analyze the impact of the Brazilian economic liberalization process between 1990 and 2002. It focuses on an account of the flows of foreign direct investment (henceforth: FDI) in the period under scrutiny. Its departure point is the view that the foregoing process offers evidence for a new mode of foreign insertion grounded on the political and economic agenda of globalization. More precisely, it advances a perspective built on the conceptual category of capitalist imperialism (HARVEY, 2005) that presupposes a complex arrangement between the State polity, the Empire and the capital accumulation process. In order to undertake the proposed task, it draws on a survey of the theoretical debate over globalization and its impact on the international system. The purpose is to contribute to an improved understanding of how Brazil is positioned within the context. Furthermore, the current work develops a broad explanatory analysis involving foreign as well as Brazilian trade and financial flows. As a result of such new stage of the Brazilian society, it argues for the idea that the adoption of liberalization principles (specifically with regard to internationalization of production) had not only affected negatively the income and employment but enables a reversed income flow (profits, dividends, royalties, intercompany interest) incompatible with the export capabilities of the involved sectors, which in turn might be conducive to challenges to external accounts and eventually hurt political autonomy of the nation